Peningkatan Bisnis UMKM Kerupuk Melalui Optimalisasi Packaging Produk - Nur Handayani; Fidiana; Hindah Mustika (Khaira Ummah, 2022)
The service carried out to 18 SMEs that focus on fish-based kerupuk business, especially payus fish has an important goal of providing direct understanding and training about the importance and benefits of packaging. Kerupuk as one of the traditional foods that has its own characteristics for cracker connoisseurs, so this needs to be maintained and improved. One of the ways to maintain it is to maintain the condition of good kerupuk that are ready to eat and still half-finished, need to be placed in the right place. The right place will be an attraction for buyers, so this is important for kerupuk packaging. This service explores how to make packaging that suits the product and makes the product still have good quality value in the eyes of buyers in particular. Due to ignorance and no previous training, so that in this service the 18 SMEs were very interested and very enthusiastic about the packaging training, they had high hopes that the products produced and packaged would get a big response from kerupuk enthusiasts. Keywords: SMEs, packaging, labelling.